Exploring key determinants of internal control weaknesses and non-compliance using audit findings in Indonesian ministries - Pratama, Aditya; Salim, Susanto (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Indonesian ministries face challenges in maintaining a strong internal control system, as demonstrated by BPK Audit findings that identified significant internal control weaknesses that led to substantial non-compliance incidents across ministries. This study examines key factors behind the weaknesses of the Internal Control System (ICS) and the non-compliance cases identified in Indonesian ministry audits from 2020 to 2022. Using a path analysis within the Structural Equation Modeling framework, we analyze the effects of age, size, budget realization, non-tax state revenue, and audit follow-up results. Our findings show that higher budget realization and non-tax state revenue contribute to ICS weakness, while younger ministries face greater ICS risks but fewer non-compliance cases. Strong audit follow-up helps reduce the number of non-compliance cases, highlighting its role in improving compliance. The study emphasizes the importance of robust internal controls and effective FUAR implementation in mitigating compliance risks and enhancing governance. It also provides new insights into the relationship between ministry characteristics, ICS weaknesses, and non-compliance cases, contributing to stronger financial management in the public sector.